Analisis peran guru bimbingan dan konseling dalam meningkatkan motivasi belajar siswa kelas 7 SMP N 1 Polanharjo tahun ajaran 2020/2021 - Rizanti, Tita diah (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
Abstract: The purpose of this study areto 1) find out how the steps in providing learning motivation at class VII students of SMP Negeri 1 Polanharjo in the 2020/2021 academic year. (2) find out the inhibiting factors of BK teachers in improving learning motivation at class VII students of SMP Negeri 1 Polanharjo for the 2020/2021 academic year, (3) know the supporting factors of BK teachers in increasing learning motivation of class VII students of SMP Negeri 1 Polanharjo in the Academic Year of 2020 /2021, (4) find out the impact of providing learning motivation on class VII students of SMP Negeri 1 Polanharjo for the 2020/2021 academic year. This study used a gualitative method with the subject and object of the research are the Principal, Guidance and Counseling teacher, class VII students of SMP Negeri 1 Polanharjo. Data collection technigues in this study through observation, interviews and documentation technigues. Data analysis in this study used three activity lines, namely reduction, data presentation and data verification. The results of the study at SMP Negeri 1 Polanharjo showed that the motivation for students in learning had been given to the maximum level. This was agreed by the students by providing information that the BK teacher had provided various ways to be motivated. The principal also supports and provides instructors so that BK teachers always provide motivation so that learning can be accepted as a whole. The obstacle faced in providing motivation is that it is difficult to meet students so that BK teachers can only monitor and provide motivation via cell-phones. Weak supervision makes students lazy to learn and unmotivated. The supporting factor for BK teachers in providing motivation is the self-will of the BK teachers because they feel responsible for students' learning motivation. The impact of providing learning motivation is that students are now more active in studying and diligently collecting assignments. Key Words: motivation, learning, increasing motivation